Hedging cross border commodity price risk - Varma, Jayanth, (SAGE Knowledge. Cases., 2017)
The case is about an Indian company hedging soya oil price risk in the US futures market instead of in the Indian market to take advantage of better liquidity and wider choice of hedging instruments there. A stable long run relationship (cointegration) between the two markets appeared to make the cross border hedge viable, but hedge accounting considerations appeared to stand in the way.